Maternal adverse childhood experiences, attachment style, and mental health: Pathways of transmission to child behavior problems. (July 2019) - Cooke, Jessica E.; Racine, Nicole; Plamondon, Andre; Tough, Suzanne; Madigan, Sheri
Abstract: Background: Investigations have found mothers' adverse childhood experiences (ACEs) confer an intergenerational risk to their children's outcomes. However, mechanisms underlying this transmission have only been partially explained by maternal mental health. Adult attachment insecurity has been shown to mediate the association of ACEs and mental health outcomes, yet an extension of this research to children's behavioral problems has not been examined. Objective: To examine the cascade from maternal ACEs to risk for child behavioral problems at five years of age, via mothers' attachment insecurity and mental health. Participants and setting: Participants in the current study were 1994 mother-child dyads from a prospective longitudinal cohort collected from January 2011 to October 2014. Methods: Mothers retrospectively reported their ACEs when children were 36 months of age. When children were 60 months of age, mothers completed measures of their attachment style, depression and anxiety symptoms, and their children's behavior problems. Results: Path analysis demonstrated maternal ACEs were associated with children's internalizing problems indirectly via maternal attachment avoidance, attachment anxiety, and depression symptoms, but not directly ( β = .05, 95% CI [−.001, .10]). Maternal ACEs indirectly predicted children's externalizing problems via maternal attachment avoidance, attachment anxiety, and depression. A direct effect was also observed from maternal ACEs to child externalizing problems ( β = .06, 95% CI [.01, .11]). Conclusions: Maternal ACEs influenced children's risk for poor behavioral outcomes via direct and indirect intermediary pathways. Addressing maternal insecure attachment style and depression symptoms as intervention targets for mothers with histories of ACEs may help to mitigate the intergenerational transmission of risk.